Investigation of the Rheological Characteristics of Asphalt Modified from Medical Mask Waste Fibers - Ananda Putra, I Gusti Agung; Thanaya, I Nyoman Arya; Ariawan, I Made Agus; Ciawi, Yenni (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Masks are essential for preventing people from breathing in dangerous compounds and airborne pollutants. On the other hand, incorrect mask disposal presents a serious environmental risk. Medical masks are mostly made of polypropylene and are formed of three layers: a central layer of melt-blown material, an outer layer of waterproof non-woven fabric, and an interior layer. This research aims to determine the effect of medical mask waste fiber on the rheological characteristics of asphalt. In terms of the rheological characteristics of asphalt, the addition of asphalt will decrease the penetration, ductility, specific gravity, and lost on heating, and increase the viscosity, softening point, and flash point. The positive impact is that the inclusion of mask waste results in increased asphalt hardness, enhancing resistance to rutting. On the other hand, the negative impact is that the inclusion of masking waste will reduce the resistance to cracking due to the reduced elasticity.